Senarai semak garis panduan perjanjian penswastaan tanah negeri Johor - Jamian, Mohd. Anizam (2016)
Land development through privatisation is a privatisation concept which involve the development of Government land through collaboration between the Government and the private entity. In order to ensure the land development project through privatisation really brings a benefits and profitable return to the Government, detailed documented agreement must be signed before the project take off. Only with the comprehensive documented agreement all rights and liabilities of the parties involve is protected, and so on to ensure the smooth process, maintain supervision and at last the handover of a successfull project. This research contains three objectives, which is to research and analyse all privatisation related issues that bring losses to the Government. The second objectives is to verify the best mechanism in preparing an agreement for land development through privatisation, and the third objectives is to suggest the check list for guide lines in land development through privatisation agreement. The finding from this research shows that the weakness in agreement aspects was the main factor for this issues. Based on the survey to the parties involved in the privatisation process and comparison to several land privatisation agreements shows that there is so many issues that been a factors to this problems. No guide lines in drafting the agreement is considered as the main factors which needs a serious attention. This research is mainly to suggest the check list for land privatisation agreement guidelines that can ensure the standardise procedures and protecting the rights of the State Government in Land Privatisation Agreement.